Pengaruh Persepsi Merek, Harga, dan Kualitas Produk Terhadap Keputusan Pembelian Sepeda Motor di Teguh Jaya Motor Purwodadi - Irvan Setyo Hendriyanto; Edy Purwo Saputro (VALUE, 2023)
This study aims to analyze Brand Perception, Price, and Product Quality on Motorcycle Purchasing Decisions at Teguh Jaya Motor Purwodadi. This research is quantitative in nature. To obtain accurate data, primary data is taken from a questionnaire that will be given to Teguh Jaya Motor Purwodadi buyers and the public via Google form. The independent variables in the study were Brand Perception, Price, and Product Quality. While the dependent variable in this study is the Purchase Decision. This study uses multiple linear regression analysis to see if there is an effect of brand perception, price, and product quality on purchasing decisions. The object of analysis in this study is the target buyers at Teguh Jaya Motor Purwodadi. The sample of this study was buyers at Teguh Jaya Motor Purwodadi, totaling 102 people. The sampling technique in this study used purposive sampling technique. The data analysis method uses SPSS software. The findings of this study obtained that Brand Perception (X1) has a significant positive effect on purchasing decisions. Price (X2) has a significant positive effect on purchasing decisions. Product Quality (X3) has a significant positive effect on purchasing decisions. So Brand Perception, Price, and Product Quality have a significant positive influence on the variable Purchasing Decision for motorbikes at Teguh Jaya Motor Purwodadi. It can be concluded that to increase the number of purchases, Brand Perception and Product Quality must be improved, while the pricing strategy takes into account the prices of competing products in the market.